Instilling the Value of Defending the State through Animated Educational Pocket Books for Early Childhood - Teguh Soedarto; Hamidah Hendrarini; Alvian Dwiangga Wijaya; Teddy Prima Anggriawan; Anajeng Esri Edhi Mahanani; Zuhda Mila Fitriana (Future Science, 2021)
The nation's generation is a pillar or pillar of the country's future development. Ensuring the education of the nation's generation means seeking superior seed breeding for future development. Early childhood or Kindergarten age is an age group that in terms of education is easy to form. Early age is a golden age, where at this time children's brain development develops very rapidly. This period is also critical in the development of children. This event occurs once in a human's lifetime. Therefore, at this time children must be stimulated so that their development becomes optimal, for the sake of their future. One of the ways to provide stimulation is through education. The importance of children's education from an early age is also based on Law no. 20 of 2003 concerning the National Education System, which states that early childhood education is one of the coaching efforts aimed at children from birth to 6 years which is carried out through the provision of educational stimuli to help physical and spiritual growth and development so that children have readiness in entering further education level (Article 1 point 14). With the education of national insight, it is hoped that later the children will grow into generations of nations who love their country and homeland. On the other hand, if children are not equipped with strong national insight values, in the future they will be very vulnerable to being